AVERSION TO THE MEAN - Strandburg, Walter L. (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1972)
Average grades suggest to some students that one’s potential is mediocre. This is threatening to students whose feelings of worth and significance are closely related to their academic achievements. The mean spells mediocrity and some students will fail rather than be mediocre.